Preventive Antibiotic Prescribing Habits among Professionals Dedicated to Oral Implantology: An Observational Study - Angel Orión Salgado-Peralvo; Naresh Kewalramani; Juan Francisco Peña-Cardelles; María Victoria Mateos-Moreno; Loreto Monsalve-Guil; Álvaro Jiménez-Guerra; Iván Ortiz-García; Eugenio Velasco-Ortega (MDPI AG, 2021)
The prescription of preventive antibiotics (PA) in oral implantology is a controversial issue. The study aimed to determine the prescribing habits of PA in professionals dedicated to oral implantology in various treatments in healthy and at-risk patients. This is a cross-sectional observational study based on the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines. An electronic survey consisting of 4 blocks of questions was sent to members of the Spanish Society of Implants. The data were analyzed using descriptive analysis. A total of 303 participants (20.8%) responded to the questionnaire. One percent never prescribed PA, 55.4% prescribed them always, and 43.6% prescribed them sometimes. Ninety-six percent administered them preoperatively, while 92.4% administered them postoperatively. The most commonly used antibiotic is amoxicillin followed by amoxicillin with clavulanic acid (875/125 mg). Clindamycin is the most commonly administered antibiotic in patients with allergies. Professionals dedicated to oral implantology frequently prescribe PA in both healthy and at-risk patients, especially perioperatively. Immediate implant placement, sinus lifts, bone regeneration, and multiple implant placement are the treatments in which PA are most commonly prescribed, as well as in patients with heart valve prostheses or a history of bacterial endocarditis and immunodeficiency.